The link between corporate philanthropy and board of directors - Md Hashim, Mohd Farid Asraf; Md Yusof, Mohd 'Atef (2017)
Corporate involvement in addressing social issues is in line with the Malaysian government's aspirations as postulated in the Government Transformation Plan and Vision 2020. As one of the key activities in the realm of corporate social responsibility, corporate philanthropy benefits various stakeholders, especially the community while enhancing corporate's reputation, shareholders value, financial performance and sustainability of the company. Relevance to this sense, the board of directors plays a vital role in determining the policies and decisions on corporate philanthropy since the choice of implementing such initiative is within the top management discretion. Their engagement in setting the direction of the corporate philanthropic programs could help to ensure a good fit with other business activities without disregarding the needs of the surrounding community. This, the article presents a theoretical proposition based on the resource dependency theory in discussing the link between the board of directors' characteristics and corporate philanthropy involvement. The specific aim of this article is to discuss the probable relationship between women directors, directors' level of education, directors with community influential and the execution of corporate philanthropy initiatives. This article contributes to the literature by offering initial insights that may help firms and stakeholders in selecting future corporate leaders as their background, education and experience may shape the key social responsibility initiatives such as corporate philanthropy.